Peningkatan Literasi Terhadap Keamanan Digital dan Gaya Hidup Sehat Aktif melalui Edukasi terhadap Siswa SMP - Sholikhah, Anindya Mar'atus; Yuliastrid, Dita; Mustar, Yetty Septiani; Susanto, Indra Himawan; Noordia, Anna (Laksana Olahraga, 2025)
Abstract: Adolescents are among the most active users of social media, often exceeding two hours of screen time daily. However, this high level of use is not matched by adequate digital literacy, leaving them vulnerable to cybercrimes and cyberbullying. This community service aims to enhance students’ awareness and literacy of digital security while promoting active and healthy lifestyle. Materials were delivered using PowerPoint presentations and supporting booklets. A total of 32 grade XI students participated actively and enthusiastically. Their engagement was evident through their participation in discussions. Post-activity evaluations indicated an improvement in students’ comprehension of digital literacy and healthy living practices. These outcomes reflect a growing interest and awareness among adolescents regarding the importance of digital well-being and lifestyle health. The community service activity was successfully implemented, achieving its intended goals. To maintain momentum and relevance, similar initiatives should be conducted regularly. Furthermore, sustained collaboration among schools, parents, and the wider community is essential to ensure that the knowledge and habits promoted during the program are continuously reinforced and applied in daily life.